Genome-wide analysis of Epstein-Barr virus identifies variants and genes associated with gastric carcinoma and population structure. Issue 10 (October 2017) - Yao, Youyuan; Xu, Miao; Liang, Liming; Zhang, Haojiong; Xu, Ruihua; Feng, Qisheng; Feng, Lin; Luo, Bing; Zeng, Yi-Xin
Epstein–Barr virus is a ubiquitous virus and is associated with several human malignances, including the significant subset of gastric carcinoma, Epstein–Barr virus–associated gastric carcinoma. Some Epstein–Barr virus–associated diseases are uniquely prevalent in populations with different geographic origins. However, the features of the disease and geographically associated Epstein–Barr virus genetic variation as well as the roles that the variation plays in carcinogenesis and evolution remain unclear. Therefore, in this study, we sequenced 95 geographically distinct Epstein–Barr virus isolates from Epstein–Barr virus–associated gastric carcinoma biopsies and saliva of healthy donors to detect variants and genes associated with gastric carcinoma and population structure from a genome-wide spectrum. We demonstrated that Epstein–Barr virus revealed the population structure between North China and South China. In addition, we observed population stratification between Epstein–Barr virus strains from gastric carcinoma and healthy controls, indicating that certain Epstein–Barr virus subtypes are associated with different gastric carcinoma risks. We identified that the BRLF1, BBRF3, and BBLF2/BBLF3 genes had significant associations with gastric carcinoma. LMP1 and BNLF2a genes were strongly geographically associated genes in Epstein–Barr virus. Our study provides insights into the genetic basis of oncogenic Epstein–Barr virus for gastric carcinoma, and the genetic variants associated with gastric carcinoma can serve as biomarkers for oncogenic Epstein–Barr virus.